Uncovering the genetic basis of antiviral polyketide limocrocin biosynthesis through heterologous expression - Sofiia Melnyk; Marc Stierhof; Dmytro Bratiichuk; Franziska Fries; Rolf Müller; Yuriy Rebets; Andriy Luzhetskyy; Bohdan Ostash (Microbial Cell Factories)
Abstract Background Streptomyces roseochromogenes NRRL 3504 produces clorobiocin, an aminocoumarin antibiotic that inhibits DNA replication. No other natural products have been isolated from this bacterium so far, despite the presence of a rich repertoire of specialized metabolite biosynthesis gene clusters (smBGCs) within its genome. Heterologous expression of smBGCs in suitable chassis speeds up the discovery of the natural products hidden behind these sets of genes. Results In this work we focus on one intriguing smBGC of NRRL 3504 bearing some similarity to gene clusters involved in production of manumycin family polyketides. Through heterologous expression in Streptomyces chassis strains S. albus Del14 and S. lividans ΔYA9, this smBGC (hereafter referred to as lim BGC) was shown to direct the production of unusual polyketide limocrocin (LIM) known for its ability to interfere with viral reverse transcriptases. The organization of lim BGC, data on the structures of revealed metabolites as well as manipulations of lim genes allowed us to put forward an initial hypothesis about a biosynthetic pathway leading to LIM. We provide initial data on two LIM derivatives as well as updated NMR spectra for the main product. Conclusion This study reveals the genetic control of biosynthesis of LIM that remained hidden for the last 70 years. This, in turn, opens the door to biological routes towards overproduction of LIM as well as generation of its derivatives.